Desenvolvimento de nanosistemas farmacêuticos para terapia gênica - Veríssimo, Lourena Mafra (2011)
Gene therapy is one of the major challenges of the post-genomic research and it is based on the transfer of genetic material into a cell, tissue or organ in order to cure or improve the patient s clinical status. In general, gene therapy consists in the insertion of functional genes aiming substitute, complement or inhibit defective genes. The achievement of a foreigner DNA expression into a population of cells requires its transfer to the target. Therefore, a key issue is to create systems, vectors, able to transfer and protect the DNA until it reaches the target. The disadvantages related to the use of viral vectors have encouraged efforts to develop emulsions as non-viral vectors. In fact, they are easy to produce, present suitable stability and enable transfection. The aim of this work was to evaluate two different non-viral vectors, cationic liposomes and nanoemulsions, and the possibility of their use in gene therapy. For the two systems, cationic lipids and helper lipids were used. Nanoemulsions were prepared using sonication method and were composed of Captex® 355; Tween® 80; Spam® 80; cationic lipid, Stearylamine (SA) or 1,2-dioleoyl-3-trimethylammoniumpropane (DOTAP) and water (Milli-Q®). These systems were characterized by average droplet size, Polidispersion Index (PI) and Zeta Potential. The stability of the systems; as well as the DNA compaction capacity; their cytotoxicity and the cytotoxicity of the isolated components; and their transfection capacity; were also evaluated. Liposomes were made by hydration film method and were composed of DOTAP; 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), containing or not Rhodaminephosphatidylethanolamine (PE- Rhodamine) and the conjugate Hyaluronic Acid DOPE (HA-DOPE). These systems were also characterized as nanoemulsions. Stability of the systems and the influence of time, size of plasmid and presence or absence of endotoxin in the formation of lipoplexes were also analyzed. Besides, the ophthalmic biodistribution of PE-Rhodamine containing liposomes was studied after intravitreal injection. The obtained results show that these systems are promising non-viral vector for further utilization in gene therapy and that this field seems to be very important in the clinical practice in this century. However, from the possibility to the practice, there is still a long way